Method for visualizing the shear process of rock joints using 3D laser scanning and 3D printing techniques - Man Huang; Chenjie Hong; Peng Sha; Shigui Du; Zhanyou Luo; Zhigang Tao (Journal of Rock Mechanics and Geotechnical Engineering, 2023)
This study presents a visualized approach for tracking joint surface morphology. Three-dimensional laser scanning (3DLS) and 3D printing (3DP) techniques are adopted to record progressive failure during rock joint shearing. The 3DP resin is used to create transparent specimens to reproduce the surface morphology of a natural joint precisely. The freezing method is employed to enhance the mechanical properties of the 3DP specimens to reproduce the properties of hard rock more accurately. A video camera containing a charge-coupled device (CCD) camera is utilized to record the evolution of damaged area of joint surface during the direct shear test. The optimal shooting distance and shooting angle are recommended to be 800 mm and 40°, respectively. The images captured by the CCD camera are corrected to quantitatively describe the damaged area on the joint surface. Verification indicates that this method can accurately describe the total sheared areas at different shear stages. These findings may contribute to elucidating the shear behavior of rock joints.